2012
DOI: 10.3892/ijo.2012.1646
|View full text |Cite
|
Sign up to set email alerts
|

Topographic and quantitative relationship between prostate inflammation, proliferative inflammatory atrophy and low-grade prostate intraepithelial neoplasia: A biopsy study in chronic prostatitis patients

Abstract: Inflammatory processes are important components in the pathogenesis of many human cancers. According to the ‘injury and regeneration’ model for prostate carcinogenesis, injury caused by pathogens or pro-inflammatory cytotoxic agents would trigger proliferation of prostatic glandular cells, leading to the appearance of epithelial lesions named ‘Proliferative Inflammatory Atrophy’ (PIA). Inflammatory cells infiltrating the prostate would release genotoxic reactive oxygen species, leading atrophic cells to neopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…This suggestion is based on the following findings: i) Morphological overlap between PIA and HGPIN; ii) the phenotypes of many of the cells in PIA are most consistent with that of immature secretory-type cells, similar to that of the cells of HGPIN; and iii) PIA, HGPIN and carcinoma all occur with high prevalence in the peripheral zone and low prevalence in the central zone of the prostate. In the present study on needle-biopsy specimens, a close topographic association between PIA/PAH and HGPIN was observed, in agreement with the findings in previous studies (18,21). …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This suggestion is based on the following findings: i) Morphological overlap between PIA and HGPIN; ii) the phenotypes of many of the cells in PIA are most consistent with that of immature secretory-type cells, similar to that of the cells of HGPIN; and iii) PIA, HGPIN and carcinoma all occur with high prevalence in the peripheral zone and low prevalence in the central zone of the prostate. In the present study on needle-biopsy specimens, a close topographic association between PIA/PAH and HGPIN was observed, in agreement with the findings in previous studies (18,21). …”
Section: Discussionsupporting
confidence: 93%
“…This shift is present in most of the carcinoma precursor lesions, including HGPIN. It has long been hypothesized that PIA may be a precursor of prostate cancer, as several studies have reported a morphological transition from PIA to HGPIN (18,21). This suggestion is based on the following findings: i) Morphological overlap between PIA and HGPIN; ii) the phenotypes of many of the cells in PIA are most consistent with that of immature secretory-type cells, similar to that of the cells of HGPIN; and iii) PIA, HGPIN and carcinoma all occur with high prevalence in the peripheral zone and low prevalence in the central zone of the prostate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although BPH is predominantly attributed to aging, genetic factors and hormonal disturbances (Nicholson and Ricke, 2011), a possible role of obesity, diet and life style is also under investigation (Tewari et al, 2012;Goluch-Koniuszy et al, 2013). Similarly the significance of chronic inflammation in pathogenesis of BPH has recently emerged (Fibbi et al, 2010) and emphasized by recent publications (Vral et al, 2012;Bostanci et al, 2013;of cancer death (Brawley, 2012a). Screening programs have increased risk of diagnosis among younger men in their 40s and 50s (Brawley, 2012b).…”
Section: Introductionmentioning
confidence: 99%